Gestão estratégica e as competências gerenciais na estrutura organizacional de instituições de ensino privado: um estudo de caso em uma escola de ensino médio e educação de jovens e adultos - Romero, Ralfe Oliveira (2011)
This paper presents a case study in a high school and youth and adults, located in the city of Passo Fundo, RS, that it uses Strategic Planning in its activities. The purpose this research is to identify management skills of managers of the company under study. To reach this purpose they had been studied the origin and history of education in Brazil, one analyzed the strategic planning and organizational structure of the company and also the functions and abilities, present and expected the director, vice- director and school supervisor of the company in question. To collect data, structured interview was used with the support of open and closed questions, applied with the director, vice-director, school supervisor, teachers, students and their subordinates. With these interviews, it was possible to identify how it is organized the management structure of the company, but also to the analysis of management skills that these professionals possess and should possess, for the efficient performance of its functions and optimization of strategic management of the company.